Multichannel Superposition of Grafted Perfect Vortex Beams. Issue 30 (17th June 2022) - Ahmed, Hammad; Intaravanne, Yuttana; Ming, Yang; Ansari, Muhammad Afnan; Buller, Gerald S.; Zentgraf, Thomas; Chen, Xianzhong
Abstract: Inspired by plant grafting, grafted vortex beams can be formed through grafting two or more helical phase profiles of optical vortex beams. Recently, grafted perfect vortex beams (GPVBs) have attracted much attention due to their unique optical properties and potential applications. However, the current method to generate and manipulate GPVBs requires a complex and bulky optical system, hindering further investigation and limiting its practical applications. Here, a compact metasurface approach for generating and manipulating GPVBs in multiple channels is proposed and demonstrated, which eliminates the need for such a complex optical setup. A single metasurface is utilized to realize various superpositions of GPVBs with different combinations of topological charges in four channels, leading to asymmetric singularity distributions. The positions of singularities in the superimposed beam can be further modulated by introducing an initial phase difference in the metasurface design. The work demonstrates a compact metasurface platform that performs a sophisticated optical task that is very challenging with conventional optics, opening opportunities for the investigation and applications of GPVBs in a wide range of emerging application areas, such as singular optics and quantum science. Abstract : A single metasurface is used to generate various grafted perfect vortex beams and realize the coaxial superpositions of these beams in different channels, without relying on the complicated conventional optical setup. A compact metasurface platform can perform a sophisticated task that is nearly impossible with conventional optics, opening opportunities for emerging application areas, such as singular optics and quantum science.